2000
DOI: 10.1023/a:1011070425430
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The binding of simple carbohydrate ligands by proteins often requires affinity enhancement to attain biologically relevant strength. This is especially true for endocytotic receptors and the molecules that engage in the first-line of defense. For such purposes, nature often utilizes a mode of affinity enhancement that arises from multiple interactions between the binding proteins and the carbohydrate ligands, which we term glycoside cluster effect. In this review article we give a number of examples and descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
209
0
3

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 423 publications
(219 citation statements)
references
References 37 publications
7
209
0
3
Order By: Relevance
“…They found that the residual inhibition by the R118 mutant was also sialic acid-dependent. These data indicate that the R118-mutant MAG retains sufficient sialic acid binding to inhibit neurite outgrowth when the protein is expressed in a highly multivalent form on the surface of CHO cells (36).…”
Section: Discussionmentioning
confidence: 73%
“…They found that the residual inhibition by the R118 mutant was also sialic acid-dependent. These data indicate that the R118-mutant MAG retains sufficient sialic acid binding to inhibit neurite outgrowth when the protein is expressed in a highly multivalent form on the surface of CHO cells (36).…”
Section: Discussionmentioning
confidence: 73%
“…The multiple subunits may endow multivalent binding properties to the MBP. This is of significant interest because it is well established that high affinity multivalent binding capable of clustering the receptors is often required for the biological function of most lectins (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, sialic acid binding lectins, which also include several viral glycoproteins and bacterial toxins (2,4), as well as the mammalian lectin superfamilies such as the siglecs (5) and selectins (6), bind to their receptor with relatively high affinity due to the multivalent nature of these molecules, thus alleviating the low intrinsic affinity that most protein-carbohydrate interactions are associated with (7,8). Generally, association constants (K a ) for the binding of monovalent and divalent sialosides by such lectins can reach 10 4 …”
mentioning
confidence: 99%